The Membrane Transporter OAT7 (SLC22A9) Is Not a Susceptibility Factor for Osteoporosis in Europeans - Nies, Anne T.; Weiss, Stefan; Schaeffeler, Elke; Hannemann, Anke; Völker, Uwe; Wallaschofski, Henri; Schwab, Matthias (Frontiers in Endocrinology, 2020)
Bone production, maintenance and modeling is a well-balanced process involving mineralization by osteoblasts and resorption by osteoclasts. Sex steroid hormones, including their conjugated forms, contribute majorly to maintaining this balance. Recently, variants in the SLC22A9 gene have been associated with osteoporosis in Korean females. We had recently shown that SLC22A9, encoding organic anion transporter 7 (OAT7), is an uptake transporter of estrone sulfate and identified several genetic variants in Europeans leading to functional consequences in vitro. We therefore hypothesized that SLC22A9 genetic variants may contribute to the pathophysiology of osteoporosis in Europeans. To test this hypothesis, we examined the associations of SLC22A9 variants with bone quality, fractures and bone turnover markers. We genotyped SLC22A9 variants in 5701 (2930 female) subjects (age range 20-93 years) extracted from the population-based Study of Health in Pomerania (SHIP and SHIP-TREND) covered by the Illumina Infinium HumanExome BeadChip version v1.0 (Exome Chip). Descriptive data (e.g. history of fractures), ultrasonography of the calcaneus as well as serum concentrations of carboxy-terminal telopeptide of type I collagen, amino-terminal propeptide of type I procollagen and vitamin D were determined. Comprehensive statistical analyses revealed no association between low-frequency and rare SLC22A9 variants and bone quality, fractures and bone turnover markers. Our results indicate that single genetic SLC22A9 variants do not have a major impact on osteoporosis risk prediction in Europeans, yet findings need to be replicated in larger-scale studies.